EFFECTS OF MONACOLIN K ON INFLAMMATION, OXIDATIVE STRESS, AND ENDOTHELIAL FUNCTION IN PATIENTS WITH MODERATE HYPERLIPIDEMIA - Mammadova, G.G.; Gahramanova, S.M.; Azizov, V.A. (World of Medicine and Biology, 2025)
The purpose to investigate the effect of a 12-week course of monacolin K and rosuvastatin on parameters of lipid profile, inflammatory markers, oxidative stress indices, and vascular function in patients with dyslipidemia. 60 patients with dyslipidemia were randomly divided into two equal groups: one group received monacolin K, the second one –rosuvastatin. Biomarkers were measured both before and after 12 weeks of treatment, including low-density lipoprotein cholesterol, high-sensitivity C-reactive protein, malondialdehyde, and intercellular adhesion molecule-1. Both groups showed statistically significant improvement compared to baseline (p
Keywords: monacolin K; rosuvastatin; dyslipidemia; low-density lipoprotein cholesterol; high-sensitivity C-reactive protein; malondialdehyde; and intercellular adhesion molecule-1